Diagnosis of Open-Switch and Current Sensor Faults in PMSM Drives Through Stator Current Analysis - Khojet El Khil, Sejir (2020)
Fault detection and fault accommodation, as well as fault tolerance, are important issues in closed-loop controlled three-phase converters. For such systems, power semiconductors and sensors are the most affected components by the occurrence of failures. Therefore, fault diagnosis and remedial operating strategies involving such components are highly required. In this paper, a new reliable approach is proposed, which aims to diagnose current sensor faults and power semiconductor open-circuit faults in permanent magnet synchronous motor drives. The proposed fault diagnosis scheme uses only the measured currents, which makes it suitable for real-time implementation. The performance of the proposed technique is analyzed through experiments.